Performance-oriented architecture : rethinking architectural design and the built environment - Hensel, Michael (Hoboken, N.J. : Wiley, 2013)
Architecture is on the brink. It is a discipline in crisis. Over the last two decades, architectural debate has diversified to the point of fragmentation and exhaustion. What is called for is an overarching argument or set of criteria on which to approach the design and construction of the built environment. Here, the internationally renowned architect and educator Michael Hensel advocates an entirely different way of thinking about architecture. By favouring a new focus on performance, he rejects longstanding conventions in design and the built environment. This not only bridges the gap between academia and practice, but, even more significantly, the treatment of form and function in design. It also has a far-reaching impact on knowledge production and development, placing an important emphasis on design research in architecture and the value of an interdisciplinary approach./ Though 'performance' first evolved as a concept in the humanities in the 1940s and 1950s, it has never previously been systematically applied in architecture in an inclusive manner. Here Michael Hensel offers Performance-Orientated Architecture as an integrative approach to architectural design, the built environment and questions of sustainability. He highlights how core concepts and specific traits, such as climate, material performance and settlement patterns, can put architecture in the service of the natural environment. A wide range of examples are cited to support his argument, from traditional sustainable buildings, such as the Kahju Bridge in Isfahan and the Topkapi Palace in Istanbul to more contemporary works by Cloud 9, Foreign Office Architects, Steven Holl and OCEAN.
Second-Degree Auxiliarity: Supplementary ArchitecturesFirst-Degree Auxiliarity: Embedded Architectures; Multiple Grounds and Settlement Patterns; Chapter 6: The Road(s) Ahead; Bibliography; Key Search Terms; Picture Credits
Title from resource description page (Recorded Books, viewed November 21, 2013).
Keywords: Architecture; ARCHITECTURE -- General; Architecture; Electronic books; Electronic books